Chemistry essentials for dummies - Moore, John T. , 1947- (For dummies, 2010)
Whether studying chemistry as part of a degree requirement or as part of a core curriculum, students will find Chemistry Essentials For Dummies to be an invaluable quick reference guide to the fundamentals of this often challenging course